RANCANG BANGUN SISTEM DETONATOR ROBUST PADA FUZE PROXIMITI BPPT - Muamar Khadafi; Ade Purwanto; Tris Dewi Indraswati (Universitas Tarumanagara, 2021)
Fuze is a device to ensure the safety, to prepare and to detonate a warhead, with a certain requirements which is set from the design of the mechanism. The design of the fuze requires that the system must be robust so that it will not endangered the handling, transporting and storing the warhead. In addition to that, a fuze must be confirmed that it will trigger the explosion of the warhead when it reaches the target. The sensitive application of the fuze in the military world makes the design mostly confidential and only a little portion is revealed in the media and scientific article. All of this problem contribute to the inability of Indonesia to produce it’s own fuze, either the mechanic, chemical or electro-mechanic version of it. All of Indonesian warhead uses imported fuze from overseas, which makes Indonesian military depends on other countries. In this study, prototype of a robust detonator system for a proximity fuze, a type of electro-mechanic fuze that uses a range-sensor to determine the detonation time of the warhead, is made. The system was made using an SF30C Laser as the proximity sensor and a detonation system utilizing an electric signal. The Printed Circuit Board (PCB) was custom built with the majority of components using the Surface Mount Devices (SMD) design style, a Lithium Polymer type battery with a voltage of 7.4 VDC was used as the power supply. The Arduino Pro-Micro was used to be the processor, which was placed on the PCB using a Pin Through Hole (PTH) system. Several configurations have been tested and documented.The detonation system using double-PhotoMOS was proved to be the most reliable compared to several other systems. PhotoMOS was configured so that when it was activated, Proximity Fuze would be able to send an electric current to the detonator, so that the detonator will be burt. The results of experiments shows that the Photomos can trigger detonator explosions at an average error target distance of 1,15%. Thus the Proximiti fuze prototype can be said to work well and is possible to be applied in the defense industry ABSTRAK:Fuze merupakan perangkat untuk mengamankan, menyiapkan dan meledakan suatu hulu ledak dengan persyaratan yang telah ditetapkan pada perancangan mekanisme kerjanya. Desain Fuze mewajibkan agar sistem yang digunakan robust sehingga tidak membahayakan penanganan, pemindahan dan penyimpanan hulu ledak. Di sisi lain, fuze harus dipastikan bisa meledakkan hulu ledak ketika mencapai sasaran. Penggunaan fuze yang sangat sensitif di dunia militer membuat desain Fuze bersifat rahasia, dan hanya sedikit yang diulas secara detil di media maupun artikel ilmiah. Beberapa masalah ini membuat Indonesia belum mampu membuat Fuze, baik tipe mekanik, kimia maupun elektronik. Seluruh hulu ledak yang menggunakan Fuze di Indonesia menggunakan Fuze impor dari luar negri, menjadikan militer Indonesia bergantung kepada negara lain.Dalam studi ini dibuat prototipe sistem detonator handal untuk fuze Proximiti, yaitu salah satu tipe Fuze elektro-mekanik, yang menggunakan sensor jarak untuk menentukan waktu peledakan hulu ledaknya. Sistem dibuat menggunakan Laser SF30C sebagai sensor proximity dan sistem detonasi berupa sinyal elektrik. Printed Circuit Board (PCB) dibangun secara khusus dengan mayoritas komponen menggunakan gaya desain Surface Mount Devices (SMD), catu daya menggunakan baterai tipe Lithium Polymer dengan tegangan 7.4 VDC. Prosesor menggunakan Arduino Pro-Micro yang diletakkan pada PCB dengan sistem Pin Through Hole (PTH). Beberapa konfigurasi telah diujikan dan didokumentasikan. Sistem detonasi menggunakan double-PhotoMOS terbukti paling handal dibandingkan beberapa sistem yang lainnya. PhotoMOS dikonfigurasikan agar ketika telah aktif, fuze Proximiti dapat mengalirkan arus listrik kepada detonator, sehingga detonator akan terbakar. Hasil percobaan yang dilakukan fuze Proximiti dapat memicu ledakan detonator pada rata – rata error jarak dari target sebesar 1.15%. Dengan demikian prototipe fuze Proximiti dapat dikatakan bekerja dengan baik dan dimungkinkan untuk dapat direalisasikan dalam industri pertahana